Moderasi Beragama: Implementasi Nilai Toleransi Beragama pada Pembelajaran Matematika di IAIN Curup - Irsal, Irni Latifa; Putri, Dini Palupi; Marsandha, Tasha; Rahayu, Mita; Diahandini, Safira (ARITHMETIC: Academic Journal of Math, 2024)
This research aim to analyze the implementation of tolerance in mathematics learning at Tadris Mathematics of IAIN Curup as one of the steps to monitor the realization of national unity. A qualitative descriptive method approach was used to explore information regarding the implementation of tolerance. Observation, questionnaires, and documentation are used as data mining tools. Total of 35 students and 4 lecturers became informants to this research. The research result show that there are three aspects of tolerance, namely respecting differences of any kind, whether opinions, ethnic, religious, physical, economic, social, and cultural views; provide freedom/provide space for creativity, opinion, and fulfill individual rights as human beings within appropriate norms and religion; and upholding discussion/deliberation/consensus (being open to differences) is well implemented in mathematics learning at Tadris Mathematics of IAIN Curup. Implementation is carried out in the learning process, semester lesson plan, teaching/reference materials that used, as well as evaluation tasks that given to students.